Calreticulin Expression in Human Non-Small Cell Lung Cancers Correlates with Increased Accumulation of Antitumor Immune Cells and Favorable Prognosis - Fucikova, Jitka; Becht, Etienne; Iribarren, Kristina; Goc, Jeremy; Remark, Romain; Damotte, Diane; Alifano, Marco; Devi, Priyanka; Biton, Jerome; Germain, Claire; Lupo, Audrey; Fridman, Wolf Herve; et al. (Cancer research, 2016)
A high density of tumor-infiltrating mature dendritic cells (DC) and CD8(+) T cells correlates with a positive prognosis in a majority of human cancers. The recruitment of activated lymphocytes to the tumor microenvironment, primed to recognize tumor-associated antigens, can occur in response to immunogenic cell death (ICD) of tumor cells. ICD is characterized by the preapoptotic translocation of calreticulin (CRT) from the endoplasmic reticulum (ER) to the cell surface as a result of an ER stress response accompanied by the phosphorylation of eukaryotic initiation factor 2α (eIF2α). We conducted a retrospective study on two independent cohorts of patients with non-small cell lung cancer (NSCLC) to investigate the prognostic potential of CRT. We report that the level of CRT expression on tumor cells, which correlated with eIF2α phosphorylation, positively influenced the clinical outcome of NSCLC. High CRT expression on tumor cells was associated with a higher density of infiltrating mature DC and effector memory T-cell subsets, suggesting that CRT triggers the activation of adaptive immune responses in the tumor microenvironment. Accordingly, patients with elevated CRT expression and dense intratumoral infiltration by DC or CD8(+) T lymphocytes had the best prognosis. We conclude that CRT expression constitutes a new powerful prognostic biomarker that reflects enhanced local antitumor immune responses in the lung. Cancer Res; 76(7); 1746-56. ©2016 AACR.
Keywords: Cell Line, Tumor; nemalobuněčný karcinom plic; nádory plic; Calreticulin; lidé; prognóza; kohortové studie; Cohort Studies; retrospektivní studie; prospektivní studie; T-lymfocyty - podskupiny; Prospective Studies; Carcinoma, Non-Small-Cell Lung; kalretikulin; Prognosis; Lung Neoplasms; lidé středního věku; T-Lymphocyte Subsets; Retrospective Studies; Middle Aged; nádorové buněčné linie; Humans